(untitled) (Journal of Informatics Education and Research, 2025)
This study looks at how high school students in Bangalore and Kanakapura, Karnataka, use social media and how that affects their academic achievement. Concerns have been raised regarding the academic ramifications of the social media environment’s rapid proliferation, which has drastically changed teenage communication, learning, and engagement patterns. Purpose: To evaluate the connection between high school students’ academic achievement and the frequency, duration, and purpose of their social media use, as well as whether learning outcomes are affected differently by educational versus recreational use. Methodology: A quantitative research methodology was used, employing standardized questionnaires to poll 300 pupils from public and private schools. The frequency, duration, goal, and academic results of social media use were among the data gathered. To investigate the associations between variables, statistical procedures including multiple regression and Pearson correlation were used. The findings were then interpreted in light of the body of existing literature. Major Findings: Academic performance and excessive and recreational social media use are negatively correlated, while moderate and educationally motivated consumption shows a neutral or somewhat favorable correlation. To preserve academic success, the results emphasize the significance of digital literacy, responsible user conduct, and balanced technology use.